Preliminary Report on the Effect of a Lower Dose of Gonadotropin-Releasing Hormone Antagonist (Cetrorelix) on Ovarian Hyperstimulation in Lower-Weight Asian Women - Yung-Ling Chang; Yao-Yuan Hsieh; Horng-Der Tsai (Elsevier, 2006)
Objective: To determine the minimal effective daily dose of gonadotropin-releasing hormone (GnRH) antagonist in lower-weight Asian women undergoing controlled ovarian hyperstimulation (COH). Materials and Methods: A prospective randomized controlled trial of GnRH antagonist was performed. A total of 58 women with body weight of 40-50 kg accepted COH and transvaginal embryo transfer. Patients were divided into two groups: Group 1 patients (n = 28) were given a fixed cetrorelix dose of 0.2 mg/day; Group 2 patients (n = 30) were given a fixed cetrorelix dose of 0.15 mg/day. Cetrorelix was administered from menstrual day 8 until the day of human chorionic gonadotropin (hCG) administration. Serum luteinizing hormone (LH) and estradiol (E2) concentration were measured on the day of hCG administration. Gonadotropin dosages, LH and E2 concentrations, retrieved oocyte and embryo numbers, ovarian hyperstimulation syndrome (OHSS), embryo quality, and the rates of fertilization, implantation and pregnancy in both groups were compared. Results: The clinical pregnancy/implantation rates in Group 1 were higher than those in Group 2 (28.6%/10.4% vs. 20%/4.1%). The numbers of oocytes retrieved/Grade I-II embryos were higher in Group 1 than Group 2 (10.5/7.8 vs. 8.3/3.9). A lower percentage of LH surge and higher E2 levels on the day of hCG adminstration were observed in Group 1 compared to Group 2 (5.9%/1,610.8 pg/mL vs. 26.7%/1,023.6 pg/mL). There were no statistical differences between the two groups when comparing gonadotropin dosage and OHSS. Conclusion: The lowest effective dosage of cetrorelix is 0.2 mg in COH and pituitary downregulation for lower-weight Asian women.